Pengembangan Perangkat Pembelajaran Aljabar Berbasis Problem Based Learning untuk Mendukung Kemampuan Komunikasi Matematika Siswa Sekolah Menengah Pertama - Winarni, Sri; Marlina, Marlina (Edumatika, 2020)
The purpose of this research is to develop learning tools based for Algebra on Problem Based Learning (PBL) to support the mathematics communication ability of Junior High School students. Learning tools developed in this development research is students’ worksheets. The research method used is 4D model, which consists of 4 stages, namely define, design, develop, and disseminate. The results of worksheets’ validation by experts were 4,05 for the layout design and 4,19 for the content (both were categorized as valid). In addition, the students respons that the students’ worksheets were practical (with average of 3,94) and the teacher responses that these were very practical (with average of 4,23). Thus, based on the expert validation as well as the students and teacher of mathematics responses, the learning tools developed have already met the criteria of valid and practical and ready for the field testing to see its effectiveness on students’ mathematics communication ability.